Nursing perspectives about the critical gaps in public health emergency response during the COVID‐19 pandemic. Issue 1 (21st June 2022) - Norful, Allison A.; Tucker, Sharon; Miller, Pamela S.; Roberts, Haley; Kelley, Marjorie M.; Monturo, Cheryl; O'Mathúna, Dónal; Smith, Julia; Zadvinskis, Inga M.; Zellefrow, Cindy; Chipps, Esther
Abstract: Introduction: The purpose of this qualitative study was to synthesize frontline U.S. nursing perspectives about the current state of U.S. public health emergency preparedness and response. The study findings may inform public health policy change and improve future national pandemic planning and responses. Design: We conducted a secondary thematic qualitative analysis using grounded theory methodology. Methods: Data collection occurred through semi‐structured, in‐depth focus groups between July and December 2020, from 43 frontline nurses working in hospitals in four states (Ohio, California, Pennsylvania, and New York). Data were analyzed deductively, aligned with Khan et al.'s Public Health Emergency Preparedness Framework and inductively for emergent themes. Results: Three themes emerged: (1) Validation of the presence of health disparities and inequities across populations; (2) Perceived lack of consistency and coordination of messaging about pandemic policies and plans across all levels; and (3) challenges securing and allocating nursing workforce resources to areas of need. Conclusion: From a frontline nursing perspective, this study demonstrates the critical need to address health inequities and inequalities across populations, a consistent national vehicle for communication, and national plan for securing and allocating nursing workforce resources.